Music therapy in child welfare : bridging provision, protection, and participation - Krüger, Viggo (Barcelona Publishers, 2020)
Music Therapy in Child Welfare explores the relationship between children's rights and international child welfare and music therapy theory, research and practice. The purpose of the book is to contribute to an increased awareness among adults who work with children and adolescents in child welfare settings regarding music's role, music therapy, and children's rights.